2009
DOI: 10.3748/wjg.15.879
|View full text |Cite
|
Sign up to set email alerts
|

Extensive hepatic-portal and mesenteric venous gas due to sigmoid diverticulitis

Abstract: Hepatic portal venous gas is most often associated with extensive bowel necrosis due to mesenteric infarction. Mortality exceeds 75% with this condition. The most common precipitating factors include ischemia, intra-abdominal abscesses and inflammatory bowel disease. In this report, we present a 75-year-old woman with extensive hepatic portal and mesenteric venous gas due to colonic diverticulitis. She had a 10-year history of type II diabetes mellitus and hypertension. She was treated by sigmoid resection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although the presence of gas in the portal venous system was generally considered to be a serious intra-abdominal event, many benign cases have been put forward with the development of imaging modalities. Our search for reported cases of HPVG during the most recent 5 years (table 2 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] revealed that 20 of the 31 patients were treated by a nonsurgical approach, and 22 (71%) of the 31 patients recovered, suggesting that HPVG is not always a fatal sign in those patients. In addition, invasive therapy, including chemotherapy, endoscopic retrograde cholangiopancreatography, and CT-guided aspiration biopsy, was performed in 14 (45.2%) of the 31 patients before onset of HPVG.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of gas in the portal venous system was generally considered to be a serious intra-abdominal event, many benign cases have been put forward with the development of imaging modalities. Our search for reported cases of HPVG during the most recent 5 years (table 2 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] revealed that 20 of the 31 patients were treated by a nonsurgical approach, and 22 (71%) of the 31 patients recovered, suggesting that HPVG is not always a fatal sign in those patients. In addition, invasive therapy, including chemotherapy, endoscopic retrograde cholangiopancreatography, and CT-guided aspiration biopsy, was performed in 14 (45.2%) of the 31 patients before onset of HPVG.…”
Section: Discussionmentioning
confidence: 99%
“… 3,5,8–10 First described in 1955 associated in infants with necrotizing enterocolitis, 1 HPVG has since been described in numerous other clinical scenarios. Some less morbid causes of portal venous gas include ileus, 11 diverticulitis, 12,13 gastric distention, 14,15 inflammatory bowel disease (IBD), 16 hypotension post dialysis treatment, 17 decompression sickness, 18 trauma 19 and iatrogenic causes from instrumentation and recent surgery either with or without complications related the procedure. 8,20 Some benign causes of pneumatosis intestinalis, but not directly shown to cause HPVG, include high-pressure ventilation, chronic obstructive pulmonary disorder (COPD), and high dose steroids as well as numerous other conditions both organic and iatrogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel ischemia/infarction or necrosis is the commonest cause of portal vein gas and it's a dangerous abdominal condition in adults with high mortality [8]. Other less common causes are noted, and they cause less morbidity and mortality compared to bowel ischemia, a few examples of less common causes are diverticulitis [9], inflammatory bowel disease [10], pelvic abscess, ulcerated/necrotic bowel cancers, acute pancreatitis [11], COPD and high dose steroids [7]. In infants necrotizing fasciitis (commonest) and erythroblastosis fetalis have been implicated.…”
Section: A Rare Case Of Isolated Splenic Vessel Gas Post Infarctionmentioning
confidence: 99%